In vitro Anti-microbial and free radical scavenging activity of Zinc(II), Copper(II), Cobalt(II) and Cadmium(II) Ions Coordinated with N-(pyridin-4-yl)(tolu-4-yl)sulphonamide (African Journal of Biomedical Research, 2024)
The rising use of antibiotics and antioxidants in medicine and animal care has primarily contributed to antibiotic-resistant microbes, decreased oxidative stress, and prompted the hunt for novel and effective medications. This study reports the synthesis, bioactivity, and radical scavenging potential of N-(pyridin-4-yl)(tolu-4-yl)sulphonamide coordinated with zinc (II), copper (II), cobalt (II), and cadmium (II) ions. The condensation reaction of 4-aminopyridine and tosyl chloride produced the sulphonamide derivative. The complexes were synthesized by the reaction of ZnCl2 /Cu(NO3)2.6H2O, Co(NO3)2.6H2O, Cd(NO3)2.6H2O with the sulphonamide derivative. The antimicrobial analysis was conducted via the conventional method, and the free radical scavenging activity was achieved through the use of a 2,2-diphenyl-1-picrylhydrazyl (DPPH) solution. These compounds were characterized by physicochemical analysis, UV-VIS, FT-IR, NMR (1H and 13C) and LC-MS. The ligand and its new complexes were tested against gram (-) Escherichia coli, gram (-) Salmonella typhi, gram (+) Staphylococcus aureus, Aspergillus flavus, Aspergillus niger, and Saccharomyces cerevisiae. The findings revealed that some of the complexes have significant activity against some pathogens and show good free radical scavenging activity. The heterocyclic pyridine nitrogen in the sulphonamide is a good site for complaxation, and the methods employed and the synthesized compounds are viable sources of knowledge for the chemical and pharmaceutical industries. The study recommends further investigation into the formation of new complexes and their bioactivity with other clinical pathogens